2017
DOI: 10.4172/2368-0512.1000084
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and electrocardiographic pattern in two rural communities of Osun State in South West Nigeria

Abstract: The burden of cardiovascular disease (CVD) in the world is enormous and growing, and the majority of those affected are in the developing countries (1,2). In 2002, it was estimated that 29% of deaths worldwide (16.7 million deaths) were due to CVD and that 43% of global morbidity and mortality, measured in disability-adjusted life years (DALYS) was caused by CVD (3). Furthermore, 78% of global mortality and 86% of mortality and morbidity from CVD occurs in developing countries (3). It is estimated that by 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They also found that increasing blood glucose was associated with high blood pressure. Akinwusi and colleagues also found 7.3 % to have diabetes mellitus in another study in Osun state Nigeria [17].…”
Section: Discussionmentioning
confidence: 87%
“…They also found that increasing blood glucose was associated with high blood pressure. Akinwusi and colleagues also found 7.3 % to have diabetes mellitus in another study in Osun state Nigeria [17].…”
Section: Discussionmentioning
confidence: 87%
“…Prevalence of left ventricular hypertrophy (12.5%) in a previous study was used. 8 Tolerable margin of error was set at 5% and a non-response rate of 10% was envisaged among the respondents and corrected for.…”
Section: Sample Size Determinationmentioning
confidence: 99%